Sequestration efficiency in the iron‐limited North Atlantic: Implications for iron supply mode to fertilized blooms. Issue 13 (8th July 2014) - Le Moigne, Frédéric A. C.; Moore, C. Mark; Sanders, Richard J.; Villa‐Alfageme, Maria; Steigenberger, Sebastian; Achterberg, Eric P.
Abstract Estimates of the amount of carbon sequestered in the ocean interior per unit iron (Fe) supplied, as quantified by the sequestration efficiency (Ceffx), vary widely. Such variability in Ceffx has frequently been attributed to estimate uncertainty rather than intrinsic variability. Here we derive new estimates of Ceffx for the subpolar North Atlantic, where Fe stressed conditions have recently been demonstrated. Derived values of Ceffx from across the region, including areas subject to atypical external Fe fertilization events during the year of sample collection (2010), ranged from 17 to 19 kmol C (mol Fe−1). Comparing these estimates with values from other systems, considered in the context of variable bloom durations in the different oceanographic settings, we suggest that apparent variability in Ceffx may be related to the mode of Fe delivery.